miR-936 Suppresses Cell Proliferation, Invasion, and Drug Resistance of Laryngeal Squamous Cell Carcinoma and Targets GPR78 - Lin, Xi-Jun; Liu, Hui; Li, Pei; Wang, Hai-Feng; Yang, An-Kui; Di, Jin-Ming; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Yuan, Meng-Ling; Xing, Zi-Hao; Wei, Meng-Ning; et al. (Frontiers in Oncology, 2020)
MicroRNAs (miRs) play important roles in cancer. MiR-936 has been reported to suppress glioma and non-small cell lung cancer cell proliferation and invasion. However, the role of miR-936 in laryngeal squamous cell carcinoma (LSCC) is still unknown. In our present study, we have demonstrated that miR-936 was significantly downregulated in LSCC tissues compared with adjacent normal tissues. Furthermore, overexpression of miR-936 inhibited the proliferation, migration, invasion and drug resistance of LSCC cells. Moreover, miR-936 could improve the sensitivity of LSCC cells to doxorubicin and cisplatin. Additionally, GPR78 was identified as a novel target gene of miR-936 in LSCC cells. Overexpression of miR-936 significantly reduced the protein expression levels of GPR78 in LSCC cells. In summary, our study indicates that the miR-936/GPR78 axis could be both a diagnostic marker and a therapeutic target for LSCC.